Consumer Behavior in The Republic of Georgia regarding FMCG Products: The role of Russia in affecting Consumer Behavior after reaching DCFTA with EU countries - Griffin, George; Noniashvili, Maia; Enukidze, Nino (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
Until 2008, Russia was one of the major importers of Free Market Consumers Goods (FMCG) products from Georgia as well as a major exporter of FMCG products to Georgia. After conducting a large-scale aggression against Georgia in August, 2008; occupation of two territories in Georgia, ethnic cleansing of people in those territories; and giving recognition of independence to these two territories; Georgia terminated diplomatic relations with Russian Federation on September 2, 2008. After Russo-Georgian war in 2008 the amount of imported food products from Russia decreased. The aim of the research is to study Georgian consumer behavior; identify the factors which influence consumer behavior as a result of the Russo-Georgian War and The European Union Association Agreement; and to analyze the impact of the occupation of the Georgian territories had on trade relations with Russia.